Paraoxonase-like APMAP maintains endoplasmic-reticulum-associated lipid and lipoprotein homeostasis. - Paul, B.; Merta, H.; Ugrankar-Banerjee, R.; Hensley, M.R.; Tran, S.; do Vale, G.D.; Zacherias, L.; Hewett, C.K.; McDonald, J.G.; Font-Burgada, J.; Mathews, T.P.; Farber, S.A.; et al. (Developmental Cell, 2025)
Oxidative stress perturbs lipid homeostasis and contributes to metabolic diseases. Though ignored when compared with mitochondrial oxidation, the endoplasmic reticulum (ER) generates reactive oxygen species requiring antioxidant quality control. Using multi-organismal profiling featuring Drosophila, zebrafish, and mammalian hepatocytes, here we characterize the paraoxonase-like C20orf3/adipocyte plasma-membrane-associated protein (APMAP) as an ER-localized antioxidant that suppresses ER lipid oxidation to safeguard ER function. APMAP-depleted cells exhibit defective ER morphology, ER stress, and lipid peroxidation dependent on ER-oxidoreductase 1? (ERO1A), as well as sensitivity to ferroptosis and defects in ApoB-lipoprotein homeostasis. Similarly, organismal APMAP depletion in Drosophila and zebrafish perturbs ApoB-lipoprotein homeostasis. Strikingly, APMAP loss is rescued with chemical antioxidant N-acetyl-cysteine (NAC). Lipidomics identifies that APMAP loss elevates phospholipid peroxidation and boosts ceramides-signatures of lipid stress. Collectively, we propose that APMAP is an ER-localized antioxidant that promotes lipid and lipoprotein homeostasis in the ER network.